Chứng minh tan2a - sin2a .tan2a= sin2a
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\tan^2\alpha-\sin^2\alpha\cdot\tan^2\alpha\)
\(=\tan^2\alpha\cdot\left(1-\cos^2\alpha\right)\)
\(=\tan^2\alpha\cdot\left(1-\cos\alpha\right)\left(1+\cos\alpha\right)\)
\(\tan^2\alpha-\sin^2\alpha\cdot\tan^2\alpha\\ =\tan^2\alpha\left(1-\sin^2\alpha\right)=\tan^2\alpha\cdot\cos^2\alpha\\ =\dfrac{\sin^2\alpha}{\cos^2\alpha}\cdot\cos^2\alpha=\sin^2\alpha\\ =1-\cos^2\alpha=\left(1-\cos\alpha\right)\left(1+\cos\alpha\right)\)
\(\left(1+tan^2a\right)\left(1-sin^2a\right)-\left(1+cot^2a\right)\left(1-cos^2a\right)\)
\(=\left(1+\dfrac{sin^2a}{cos^2a}\right).cos^2a-\left(1+\dfrac{cos^2a}{sin^2a}\right).sin^2a\)
\(=cos^2a+sin^2a-sin^2a-cos^2a=\)\(0\)
Vậy B=0
\(\frac{sina+sin3a+sin2a}{cosa+cos3a+cos2a}=\frac{2sin2a.cosa+sin2a}{2cos2a.cosa+cos2a}=\frac{sin2a\left(2cosa+1\right)}{cos2a\left(2cosa+1\right)}=\frac{sin2a}{cos2a}=tan2a\)
\(cos^2\left(a-\frac{\pi}{4}\right)-sin^2\left(a-\frac{\pi}{4}\right)=cos\left(2a-\frac{\pi}{2}\right)\)
\(=cos\left(\frac{\pi}{2}-2a\right)=sin2a\)
\(tan3a-tan2a-tana=\frac{sin3a}{cos3a}-\frac{sin2a}{cos2a}-\frac{sina}{cosa}=\frac{sin3a.cos2a-sin2a.cos3a}{cos3a.cos2a}-\frac{sina}{cosa}\)
\(=\frac{sin\left(3a-2a\right)}{cos3a.cos2a}-\frac{sina}{cosa}=\frac{sina}{cos3a.cos2a}-\frac{sina}{cosa}=tana\left(\frac{cosa}{cos3a.cos2a}-1\right)\)
\(=tana\left(\frac{cos\left(3a-2a\right)-cos3a.cos2a}{cos3a.cos2a}\right)=tana\left(\frac{cos3a.cos2a+sin3a.sin2a-cos3a.cos2a}{cos3a.cos2a}\right)\)
\(=tana\left(\frac{sin3a.sin2a}{cos3a.cos2a}\right)=tana.tan2a.tan3a\)
\(\frac{1+sin2a}{1-sin2a}=\frac{sin^2a+cos^2a+2sina.cosa}{sin^2a+cos^2a-2sina.cosa}=\frac{\left(sina+cosa\right)^2}{\left(sina-cosa\right)^2}\)
\(=\frac{\left(\sqrt{2}cos\left(a-\frac{\pi}{4}\right)\right)^2}{\left(\sqrt{2}sin\left(a-\frac{\pi}{4}\right)\right)^2}=\frac{cos^2\left(a-\frac{\pi}{4}\right)}{sin^2\left(a-\frac{\pi}{4}\right)}=cot^2\left(a-\frac{\pi}{4}\right)\)
\(\tan^2\alpha-\sin^2\alpha.\tan^2\alpha=\tan^2\alpha\left(1-\sin^2\alpha\right)=\tan^2\alpha.\cos^2\alpha=\sin^2\alpha\)